KiKli Fit: Insights into the Development and Practice of a Physical Activity Program in Pediatric Cancer - Lisa Hillebrech; Lars Rehbein; Ann Christin Schneider; Sara Müller; Christina Schindera; Katharina Eva; Valentin Benzing (Current Issues in Sport Science)
Introduction Pediatric cancer patients are particularly vulnerable to short- and long-term side and late-effects in physical and mental health caused by their disease and its treatment (Benzing et al., 2021, 2022; Robison & Hudson, 2013).Physical activity (PA) has been shown to benefit various physical and mental health domains. Emerging research in pediatric oncology increasingly demonstrates the positive impact of PA both during and after treatment. However, PA interventions in acute care settings within Swiss pediatric oncology remain rare. Therefore, the KiKli Fit project was initiated to design and implement a tailored PA program at the Department of Pediatric Oncology and Hematology at the University Hospital Bern.